Analytical method for histamine, urocanic acid isomers, and their precursor histidine in fish sauce based on precolumn dansylation and high-performance liquid chromatography. (May 2023) - Zhong, Jian-Jun; Xia, Liping; Xue, Liuru; Liu, Boyu; Zhao, Lingling; Ye, Hua; Li, Zhanming
Abstract: Histamine food poisoning (HFP) or scombrotoxic fish poisoning is a major public health concern associated with seafood and seafood products containing copious amounts of free histidine, which may be decarboxylated into scombrotoxic histamine, the main culprit of HFP. Moreover, the deamination product of the histidine, trans -urocanic acid, is assumed to be scombrotoxic by degranulating mast cells to release endogenous histamine after isomerizing to the cis -form, as well as known to have immunosuppressive effects. In recognition of the potential health risks associated with the histidine degradatives, this work aimed to provide a method for the simultaneous determination of histidine, histamine, and urocanic acid isomers in food, based on precolumn dansylation and subsequent reversed-phase HPLC analysis. The dansylation conditions were optimized for yield with the design of experiments approach consisted of a center point-enhanced 2 4 factorial design followed by sequential steepest ascent searches. Satisfactory chromatographic separation of fish sauce was achieved within 9 min by retention modeling of both the analytes and potentially interfering peaks. The method was fully validated with limits of detection between 0.004 and 0.017 mg 100 g −1 fish sauce, and successfully applied to several fish sauce samples, in which the histamine and urocanic acid levels were found low and unlikely of concern, with correspondingly low levels of the precursor histidine. Highlights: Effective optimization of derivatization with the design of experiment approach. Efficient optimization of difficult chromatographic separation by retention modeling. Application to several fish sauce samples to show validity of method.